FAKTOR YANG BERHUBUNGAN DENGAN AKURASI DATA MAHASISWA PESERTA UJIAN DI UPBJJ-UT JAKARTA DAN MATARAM - Sadjati, Ida Malati; Pertiwi, Pepi Rospina; Yuliana, Ernik (LPPM Universitas Terbuka, 2011)
UT has implemented computerized system for registration and examination which require accurate data and information entered. This research was conducted to analyze factors related to the accuracy of students data and information on the examination. A hundred students from Jakarta and Mataram regional centers, who have taken examination on the 1st and 2nd semester in 2009, were randomly selected as respondents, but only 58 students had responded. Primary and secondary data were collected and analyzed descriptively. Results showed that most of students who took examination were 36-50 years old (48.28%), already have job (79.31%), and first registered about 5 years before the last examination (74.14%). In terms of the adminitration of registration, most of the students said that they did it by themselves (89.66%), at UTs Regional Center (50%), and before the registration period ended (100%). The result also showed that students still made mistakes in filling the examination forms, especially data about the date of birth (20.69%), students number identification (18.97%), and subject matter code (22.41%). About the role of the examination proctor, most of students commented that they had came ontime to examination room (98.28%), provide very clearl briefing (87.93%), and examining students data accurately (86.21%). Result of Rank Spearman Correlation Coefficient indicated that factors that significantly related to the accuracy of students data on the examintaion (?=0.05) are the age of students, time of registration, registration conductor, the clarity of briefing, and the accuracy of proctors in examining students data.